Severe lactation ketoacidosis presenting as a respiratory complaint - Tamlyn Hall; Eytan Shtull‐Leber; Shahid Ahmad (Journal of the American College of Emergency Physicians Open)
Abstract Ketoacidosis, a type of high anion gap metabolic acidosis, results from 1 of 3 etiologies: diabetic ketoacidosis, alcoholic ketoacidosis, or starvation ketoacidosis (SKA). In rare instances, young and otherwise healthy lactating women have been found to develop lactation ketoacidosis, a form of SKA, when the high energy requirements of breastfeeding are not met with adequate carbohydrate intake. We present the case of a 29‐year‐old woman who presented to our emergency department with respiratory distress and headache and was found to have severe lactation ketoacidosis. The patient was treated with infusions of dextrose and bicarbonate in the emergency department and medical intensive care unit. She was discharged without complication 3 days later, after nutrition and lactation consultation. This case highlights both the importance of maintaining a broad differential diagnosis that includes lactation ketoacidosis and performing a careful interview to identify patient populations at risk for this pathology.